Factors associated with cervical cancer screening among migrant women in Europe: a systematic scoping review protocol - Marques, Patrícia (2019)
Cervical cancer is the 4th most common cancer in women in Europe. Cervical cancer screening (CCS) reduces its incidence and mortality, but its effectiveness relies on the quality of screening and women's participation. Migrant women show low participation in CCS, which might compromise an early diagnosis of the disease. Since migration rates are high in Europe, it is important to understand which barriers and facilitators influence participation in CCS among migrants to develop strategies to increase their participation. The main objective of this study is to analyze existing evidence about the factors associated with CCS participation among migrant women in Europe,